Prevalence of hyperventilation in patients with asthma. (3rd August 2022) - Deenstra, Duco D.; van Helvoort, Hanneke A. C.; Djamin, Remco S.; van Zelst, Cathelijne; in't Veen, Johannes C. C. M.; Antons, Jeanine C.; Spruit, Martijn A.; van 't Hul, Alex J.
Abstract: Objective: Asthma is frequently accompanied by dysfunctional breathing of which hyperventilation has been recognized as a subtype. The prevalence of hyperventilation in stable asthma has been scantily studied using blood gas analysis. Hence, a reliable estimate of its prevalence is lacking. It is unknown whether the Nijmegen Questionnaire (NQ) is a useful screening tool for hyperventilation in asthma. Therefore, the primary aim of this study was to determine the prevalence of hyperventilation in a large sample of patients with asthma in a stable state of disease. Secondary aims were to compare the clinical characteristics between patients with and without hyperventilation, and, to examine the concurrent validity of the NQ to detect hypocapnia in patients with asthma. Methods: A real-world, observational, multicenter study was conducted. Capillary blood gas analysis was performed in adults with a confirmed diagnosis of stable asthma. A subset of patients completed the NQ. Results: A blood gas analysis was obtained in 1006 patients. In 17% of the patients an acute hyperventilation was found, and in another 23% a chronic hyperventilation was uncovered. Patients with a chronic hyperventilation blood gas were more often female, were younger and had a better spirometric outcomes. The NQ appeared not to correlate with PCO2. Conclusion: Hyperventilation is common in patients with stable asthma. Chronic hyperventilation is more often found in females of younger age and with the best spirometric outcomes compared to patients without hyperventilation. The NQ is not a suitable screening tool for the presence of hyperventilation in stable asthmatics.